2014
DOI: 10.3758/s13423-014-0699-x
|View full text |Cite
|
Sign up to set email alerts
|

Improving fluid intelligence with training on working memory: a meta-analysis

Abstract: Working memory (WM), the ability to store and manipulate information for short periods of time, is an important predictor of scholastic aptitude and a critical bottleneck underlying higher-order cognitive processes, including controlled attention and reasoning. Recent interventions targeting WM have suggested plasticity of the WM system by demonstrating improvements in both trained and untrained WM tasks. However, evidence on transfer of improved WM into more general cognitive domains such as fluid intelligenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
396
5
9

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 547 publications
(433 citation statements)
references
References 45 publications
13
396
5
9
Order By: Relevance
“…Finally, two recent meta‐analyses of 35 cognitive training studies indicated no difference between types of control groups when compared to each other. One found significant treatment group gains regardless of the type of control group (Au et al, 2015), and the second also found that the type of control group did not have a significant influence on training effects (Peng & Miller, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Finally, two recent meta‐analyses of 35 cognitive training studies indicated no difference between types of control groups when compared to each other. One found significant treatment group gains regardless of the type of control group (Au et al, 2015), and the second also found that the type of control group did not have a significant influence on training effects (Peng & Miller, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Importantly, these training-related benefits usually benefit performance on untrained similar tasks assessing the same ability as the training tasks (near transfer) and oftentimes also to performance on tasks measuring untrained related abilities (far transfer), even though these far transfer have not been reported consistently across the literature (for meta-analyses see Au et al 2015;Karbach and Verhaeghen 2014;Schwaighofer et al 2015). All in all, previous research shows that cognitive plasticity (i.e., the potential modifiability of a person's cognitive abilities) seems to be present across the lifespan, even up to very old age (Buschkuehl et al 2008;Karbach et al 2010;Li et al 2008;Schmiedek et al 2010;Zinke et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Although the idea of improving general cognitive functioning within a few weeks is enticing, there is also accumulating evidence against a generalized effect of WM training (e.g., Clark et al 2017;De Simoni and von Bastian 2017;Guye and von Bastian 2017;Sprenger et al 2013). Even on the meta-analytic level, evidence is mixed regarding the effectiveness of cognitive training in both younger and older adults (e.g., Au et al 2015;Dougherty et al 2016;Karbach and Verhaeghen 2014;Kelly et al 2014;Lampit et al 2014;Melby-Lervåg and Hulme 2013;Melby-Lervåg et al 2016;Schwaighofer et al 2015;Soveri et al 2017). Aside from design and methodological choices potentially explaining the diverging findings (e.g., Noack et al 2009;Shipstead et al 2012), many authors increasingly articulated the potentially important influence of individual differences on cognitive training trajectories and outcomes (e.g., Buitenweg et al 2012;Guye et al 2016;Könen and Karbach 2015;Shah et al 2012;von Bastian and Oberauer 2014 Individual differences in cognitive functioning (e.g., Ackerman and Lohman 2006) and learning potential (e.g., Stern 2017) accentuate with increasing age (e.g., Rabbitt et al 2004) and have been shown to be related to personality (e.g., Graham and Lachman 2012), cognition-related beliefs such as need for cognition (NFC; e.g., Fleischhauer et al 2010;Hill et al 2013), and everyday life activities (e.g., Jopp and Hertzog 2007).…”
mentioning
confidence: 99%